Bilateral Facial Paralysis and Deafness in a Child Treated for Acute Lymphoblastic Leukemia - Rafael V. Lucena; Yuri C. F. Fernandes; Débora B. Pazinatto; Rebecca C. K. Maunsell (Case Reports in Otolaryngology)
Involvement of the ear and temporal bone in acute leukemias are uncommon. We report a case of atypical mastoiditis with bilateral facial paralysis in a child diagnosed with Acute Lymphoblastic Leukemia (ALL). A 20-month-old male child was diagnosed with ALL and developed otorrhea unresponsive to antimicrobial treatment during the first week of chemotherapy followed by hearing loss, loss of balance, and bilateral facial paralysis. A CT scan of the mastoids showed cortical erosion of the temporal bone and presence of soft tissue contents filling the mastoid cells and external auditory canal bilaterally. Mastoidectomy was performed to collect material for analysis. Histopathologic examination of the material revealed an active chronic inflammatory process, with a moderate amount of plasma cells. Chemotherapy was reintroduced 3 weeks after the surgical procedure, and progressive improvement of otorrhea and imbalance was noted. Grade III House–Brackmann peripheral facial paralysis persisted on 6-month follow-up, and the patient is in rehabilitation program.